The Quality of Implementation of Academic Supervision in Vocational Secondary Schools in Teaching Factory Based Learning - Desy Anita Karolina Sembiring; Putri Ellen Gracia Risamasu (Journal of Educational Learning and Innovation (ELIa), 2024)
This research aimed to get an idea of how academic supervision activities are implemented in learning at SMK Negeri 2 Business and Management, Jayapura based on a teaching factory in the Marketing Department. The resource persons in this research were the school principal, teaching factory field coordinator teacher majoring in marketing, the deputy principal for the curriculum department, and female students majoring in marketing. The method used in this research is a descriptive qualitative approach, through observation, in-depth interviews, and documentation studies. The data obtained was analyzed using data reduction, data presentation, and conclusion. The results obtained from this research are that supervision activities have been carried out through class visits and work practice activities which have been carried out even though they have not been carried out on a scheduled basis and have only taken the form of monitoring. Apart from that, there is an assessment of student performance which the coordinator provides, there are efforts to develop learning programs by dividing block schedules and adjusting the curriculum according to industry needs, and there is feedback provided as input for improvements including transparency of profits from Esemkamart as well as monitoring of facilities and infrastructure, although there needs to be continuous improvement and more awareness regarding the implementation of occupational safety and health when carrying out the teaching factory learning process at SMK Negeri 2 Business and Management, Jayapura.